unrealistic optimism among university students - Huda Salman Marzouk; Dr. Malik Fadil Al-Quraishi (Journal of College of Education, 2024)
The research aims to identify 1-Unrealistic optimism among university students. In order to achieve the objectives of the research presented, the researcher tested the realistic optimism for the theoretical background and the adoption of the measure. For the academic year 2021/2022, and after testing and processing the data statistically using spss, the data is: 1- university students unrealistic optimism. 2-There is no difference in unrealistic optimism among university students, depending on gender (male, female), here is optimism that is not available in reality among university students, according to non-specialization (scientific, human). And based on the findings of the research, and access to this thesis and reach it, as recommended by the researcher